Dynamics Simulation and Dynamic Characteristic Analysis of Nutation Reducer based on SolidWorks and ADAMS - Xie Zhiyu; Yao Ligang; Zhang Jun; Cai Yongwu; Wu Yaqiang (Jixie chuandong)
The nutation gear drive is a new type of planetary transmission with wide application prospects.In order to improve the serviceability of the nutation reducer,it is necessary to clarify its dynamic characteristics. Taking the nutation reducer with bilateral meshing and two-stage spiral bevel gears drive as the research object,the 3 D modeling and virtual assembly of the reducer is completed based on the SolidWorks platform.The multibody dynamics model of the nutation reducer with bilateral meshing and two-stage spiral bevel gears drive is established by ADAMS,and the dynamic characteristic simulation of the reducer is carried out. The simulation results show that the rotation speed and meshing force of each gear are consistent with the theoretical values,which indicates that the proposed model can accurately predict the dynamic characteristics of the reducer,thus provides a model basis for the analysis of the dynamic characteristics and the parameter optimization design of the nutation reducer.